An Analysis of Difficulties Faced by Accounting Students in Reading English Accounting Texts - Puspa Gundary; Gusparia Gusparia (Journal of English Language and Education, 2026)
This study investigates the difficulties faced by accounting students in reading English accounting texts in an English for Specific Purposes (ESP) context. Using a descriptive qualitative design with quantitative support, the study involved 30 fourth-semester accounting students at UIN Sultan Syarif Kasim Riau. Data were collected through a reading comprehension test, a questionnaire, and semi-structured interviews. The reading test showed that all students (100%) identified the main idea correctly, but only 83.3% answered items on technical vocabulary and contextual meaning correctly. Questionnaire results indicated that sentence complexity was the greatest challenge (M = 3.53), followed by limited use of reading strategies (M = 3.40) and technical vocabulary difficulties (M = 3.37). Interviews confirmed problems with specialized terminology, complex sentences, and insufficient background knowledge. The study highlights the need for ESP instruction that integrates vocabulary development, reading strategy training, and authentic accounting materials to improve comprehension.